Post-COVID Syndrome and Tachycardia: Theoretical Base and Treatment Experience - V. I. Podzolkov; A. E. Bragina; A. I. Tarzimanova; L. V. Vasil'eva; E. P. Batrakova; N. V. Lobova; E. E. Bykova; M. M. Khachuroeva (Столичная издательская компания, 2021)
The coronavirus pandemic showed not only an increase in levels of excess morbidity and mortality in the acute phase, but also persisting symptoms 4 weeks after the onset of the disease. A review of international studies on the prevalence and diversity of the manifestations of postcoid syndrome is presented. The data on such a manifestation of post-COVID syndrome as postural orthostatic tachycardia syndrome (POTS) are accumulating. Pathogenetic mechanisms, modern diagnostic criteria and research data on the prevalence of this syndrome are presented in the article. The Canadian Cardiovascular Society has proposed medications as a treatment for POTS, including the sinus node If channel inhibitor ivabradine. Data from several studies showing the effectiveness of this drug for POTS, including after suffering COVID-19, are presented in the article. Clinical data on the prevalence of tachycardia among patients admitted to the Sechenov University hospital are presented. About 18% of patients with hypertension and 21% of patients with normal blood pressure had a high heart rate. A clinical example of the use of ivabradine in a patient after a coronavirus infection is presented. Drug interactions and individual tolerance of ivabradine in patients after coronavirus infection are being discussed. The authors put forward the hypothesis about the further prospect of using ivabradine in the treatment of clinical manifestations of postcoid syndrome on the basis of literature data and their own experience.